Legal Responsibility for Perpetrators of Premeditated Murder (Decision Study Number: 333/Pid.B/2022/PN Smg) - Ranti, Mai; Bawono, Bambang Tri (UNISSULA Semarang, 2025)
Murder is the intentional taking of another person's life, to take another person's life, a perpetrator must do something or a series of actions that result in the death of another person, with the note that the perpetrator must be aimed at the result of the death of the other person. This thesis aims to study and analyze: First, how is the construction of the crime of premeditated murder in the concept of legal certainty. Second, what is the legal responsibility for the perpetrator of the crime of premeditated murder according to Decision Number: 333 / Pid.B / 2022 / PN Smg. The approach method used in this study is a normative legal approach, the research specifications used are descriptive normative, primary and secondary data sources and using qualitative analysis. This writing is analyzed the problem is analyzed with the theory of criminal responsibility. Based on the research results, the Implementation of the Construction of the crime of premeditated murder is regulated in several related articles, namely Article 340 of the Old Criminal Code and Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code 459 of the New Criminal Code, namely relating to the punishment given to defendants of premeditated murder intentionally and with a plan in advance to take the life of another person, threatened because of premeditated murder, with the death penalty or life imprisonment or for a certain period of time for a maximum of 20 years. Legal responsibility for the perpetrator of premeditated murder according to decision number: 333/Pid.B/2022/PN Smg the defendant is legally responsible for his actions based on Article 340 of the Criminal Code, Article 76 C in conjunction with Article 80 paragraph (3) of the Republic of Indonesia Law Number 35 of 2014 concerning amendments to the Republic of Indonesia Law Number 23 of 2002 concerning Child Protection, and Law Number 8 of 1981 concerning the Criminal Procedure Code and other relevant laws and regulations. Sentencing the Defendant therefore to life imprisonment and a fine of Rp. 1,50,000,000.00 (one billion five hundred million rupiah) if the fine is not paid it will be replaced with imprisonment for: 10 (ten) months and charging the Defendant to pay court costs of Rp. 5,000.00 (five thousand rupiah)